Packaging Labeling and Marketing Strategy for Lek Dodo Goat Milk Products in Sambiroto Hamlet, Purwomartani Village, Yogyakarta - Kristina Andryani; Astri Wulandari; Felicciana Yayi Amanova (Prospect Publishing, 2023)
Lek Dodo Goat Milk is a processed goat milk product with various flavors, such as strawberry, melon, grape, chocolate, and coffee. It is a family business product that began during the early days of the COVID-19 pandemic. So far, Lek Dodo Goat's Milk has attempted to package its product in an appealing manner, but its marketing strategy is still lacking because the product is not produced in large quantities or on a regular basis. Despite the fact that this product is considered segmented because not all consumers are accustomed to drinking goat milk, the Lek Dodo Goat Milk product has the potential and opportunity to be well received by consumers. Aside from production and human resources, there are other issues in the field of marketing. In this PKM, we provide solutions to problems by designing packaging labeling with a new concept that is expected to form a brand identity more quickly and synergize with the 5P marketing mix strategy, namely Product, Price, Process, Place, and People. This strategy is expected to help Lek Dodo Goat Milk satisfy customers in their target market, add value to their business, and become a differentiator from competitors in the future.